Coagulation tests on admission correlate with mortality and morbidity in general ICU patients: An observational study. Issue 5 (30th January 2020) - Benediktsson, Sigurdur; Hansen, Claudia; Frigyesi, Attila; Kander, Thomas
Abstract : Background: It is well known that low platelet count on admission to intensive care units (ICU) is associated with increased mortality. However, it is unknown whether prothrombin time (PT‐INR) and activated partial thromboplastin time (APTT) on admission correlate with mortality and organ failure. Therefore, the aim of this study was to investigate whether PT‐INR and APTT at admission can predict outcome in the critically ill patient after adjusting for severity of illness measured with Simplified Acute Physiology Score 3 (SAPS 3). Materials and Methods: Data were retrospectively collected. APTT and PT‐INR taken on admission and SAPS 3 score were independent variables in all regression analyses. Survival analysis was done with Cox regression. Organ failure was reported as days alive and free (DAF) of vasopressors and invasive ventilation, need of continuous renal replacement therapy (CRRT) and Acute Kidney Injury Network creatinine score (AKIN‐crea). Results: A total of 3585 ICU patients were included. Prolonged APTT correlated with mortality with 95% confidence interval (CI) of hazard ratio 1.001‐1.010. Prolonged APTT also correlated with DAF vasopressor, CRRT and AKIN‐crea with 95% CI of odds ratio (OR) 1.009‐1.034, 1.016‐1.037 and 1.009‐1.028, respectively. Increased PT‐INR correlated with DAF vasopressor and DAF ventilator with 95% CI of OR 1.112‐2.014 and 1.135‐1.847, respectively. Conclusions: Activated partial thromboplastin time prolongation was associated with mortality and all morbidity outcomes except the DAF ventilator. PT‐INR increase at admission was associated with DAF vasopressor and DAF ventilator. APTT and PT‐INR at admission correlate with morbidity, which is not accounted for in the SAPS 3 model.